Editorial: aspirin and NSAID for chemoprevention of hepatocellular carcinoma—ready for their use?. Issue 6 (23rd August 2021) - Da Fonseca, Leonardo Gomes; Forner, Alejandro
LINKED CONTENT: This article is linked to Tan et al and Danta et al papers. To view these articles, visit https://doi.org/10.1111/apt.16515 and https://doi.org/10.1111/apt.16568